Deskripsi Ketangguhan Anak Usia 5-6 Tahun - Fatmawati Ake; Sri Wahyuningsi Laiya; Sulastya Ningsih (Inovasi Pendidikan dan Anak Usia Dini, 2025)
The problem in this research was to find out the importance of fostering resilience in children aged 5-6 years. This research aims to determine the resilience in children aged 5-6 years in TK State Menara Laut Kindergarten, North Leato Subdistrict, Dumbo Raya District, Gorontalo City. The research method used was qualitative descriptive. The subjects were how to identify resilience in children. The methods employed were observation, interviews, and documentation. Based on the observation results, efforts to develop resilience in children revealed that many struggled with concentration, participation in group activities, managing emotions when facing challenging tasks or situations, communicating with peers, and recovering from failures. Thus, it can be concluded that resilience not only means being immune to stress but also encompasses the ability to learn from difficult experiences, grow from the situation, and develop greater independence and emotional understanding.